2021
DOI: 10.2903/j.efsa.2021.6903
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a feed additive consisting of Bacillus velezensis DSM 15544 (Calsporin®) for piglets (suckling and weaned), pigs for fattening, sows in order to have benefit in piglets, ornamental fish, dogs and all avian species (Asahi Biocycle Co.)

Abstract: Safety and efficacy of a feed additive consisting of Bacillus velezensis DSM 15544 (Calsporin ® ) for piglets (suckling and weaned), pigs for fattening, sows in order to have benefit in piglets, ornamental fish, dogs and all avian species (Asahi Biocycle Co.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, no truly pathogenic coding genes were found in the genome of B. velezensis TJS119. Additionally, studies on B. velezensis using fish ( Gao et al, 2017 ), pig ( Bampidis et al, 2021 ), layer chicken ( Ye et al, 2020 ), and mice ( Chen et al, 2023 ) have suggested the safety of this strain controlling diseased in animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no truly pathogenic coding genes were found in the genome of B. velezensis TJS119. Additionally, studies on B. velezensis using fish ( Gao et al, 2017 ), pig ( Bampidis et al, 2021 ), layer chicken ( Ye et al, 2020 ), and mice ( Chen et al, 2023 ) have suggested the safety of this strain controlling diseased in animals.…”
Section: Discussionmentioning
confidence: 99%
“…B. velezensis strains secrete a wide array of bioactive molecules, including antimicrobial metabolites such as macrolactin, antimicrobial lipopeptides like fengycin, and digestive enzymes [ 61 ]. For this reason, B. velezensis strains have also been extensively and safely utilized as probiotics in animal feed and aquaculture additives [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Accordingly, B. velezensis has been listed by the European Food Safety Authority (EFSA) in the approved QPS (Qualified Presumption of Safety) list [ 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) has issued several opinions on the safety and efficacy of Calsporin ® as a feed additive for different species: chickens for fattening (EFSA, 2006 , 2007a ; EFSA FEEDAP Panel, 2018a ), weaned piglets (EFSA FEEDAP Panel, 2010a , 2020 ), turkeys for fattening, ducks, geese, pigeons and other game birds for meat production, ducks, geese, pigeons, game birds, ornamental and sporting birds for rearing to point of lay, turkeys reared for breeding and chickens reared for laying (EFSA FEEDAP Panel, 2010b ), laying hens and avian species for laying (EFSA FEEDAP Panel, 2015a ), ornamental fish (EFSA FEEDAP Panel, 2015b ), sows and suckling piglets (EFSA FEEDAP Panel, 2017a ), dogs (EFSA FEEDAP Panel, 2017b ), pigs for fattening (EFSA FEEDAP Panel, 2018b ), all poultry species (EFSA FEEDAP Panel, 2019a ) and for piglets (suckling and weaned), pigs for fattening, sows in order to have benefit in piglets, ornamental fish, dogs and all avian species (EFSA FEEDAP Panel, 2021 ).…”
Section: Introductionmentioning
confidence: 99%